Buckling Behaviour of Short Cylindrical Functionally Gradient Polymeric Materials - Uysal, M. U.; Kremzer, M. (POLISH ACAD SCIENCES INST PHYSICS, 2015)
In the present study, the buckling behavior of short cylindrical Functionally Gradient Polymeric Materials (FGPMs) was studied. Besides, the structure and graphite distributions of the FGPMs were investigated. Epoxy resin was used as polymeric matrix component and two types of graphite powder materials, PAM96/98 and PV60/65, were selected. Graphite powders were added in quantities of 3, 6, 9, and 12% of volume respectively. Short cylindrical FGPMs samples were manufactured by centrifugal casting method. The structure and graphite distribution of FGPMs samples were investigated by light microscope and image processing program. It was observed that the graphite distribution had varied between the inner and outer diameter. The buckling behavior of short cylindrical FGPMs was analyzed by finite element analysis. The buckling loads of FGPMs samples were predicted.
Keywords: COMBINED EXTERNAL-PRESSURE; POSTBUCKLING ANALYSIS; SHELLS; PLATES; Physics